To find the coefficients \(a\), \(b\), \(c\), and \(d\) in the given polynomial factorizations, let's analyze each polynomial one by one.
1. First Polynomial:
Given:
\[ x^2 - 6x + 8 = (ax + b)(cx + d) \]
Expanding \( (ax + b)(cx + d) \): \[ (ac)x^2 + (ad + bc)x + (bd) \]
Comparing coefficients with \(x^2 - 6x + 8\):
- Coefficient of \(x^2\): \(ac = 1\)
- Coefficient of \(x\): \(ad + bc = -6\)
- Constant term: \(bd = 8\)
From \(ac = 1\), we can have:
- \(a = 1, c = 1\) (or) \(a = -1, c = -1\)
Let's use \(a = 1\) and \(c = 1\) to find \(b\) and \(d\):
- This gives us \(1 \cdot d + 1 \cdot b = -6\) → \(d + b = -6\)
- \(bd = 8\)
From \(d + b = -6\), let's express \(d\) in terms of \(b\): \[ d = -6 - b \] Substituting into \(bd = 8\): \[ b(-6 - b) = 8 \Rightarrow -6b - b^2 = 8 \Rightarrow b^2 + 6b + 8 = 0 \] Using the quadratic formula: \[ b = \frac{-6 \pm \sqrt{36 - 32}}{2} = \frac{-6 \pm 2}{2} = -2 \quad \text{or} \quad -4 \]
If \(b = -2\): \[ d = -6 - (-2) = -4 \quad (b, d) = (-2, -4) \]
If \(b = -4\): \[ d = -6 - (-4) = -2 \quad (b, d) = (-4, -2) \]
Thus, our values are either: \((a, b, c, d) = (1, -2, 1, -4)\) or \((1, -4, 1, -2)\).
2. Second Polynomial:
Given:
\[ 3x^3 - 6x^2 - 24x = 3x(ax + b)(cx + d) \]
Factoring out the 3: \[ x^3 - 2x^2 - 8x = (ax + b)(cx + d) \]
Expanding: \[ acx^2 + (ad + bc)x + bd = x^3 - 2x^2 - 8x \]
Comparing coefficients:
- Coefficient of \(x^2\): \(ac = 1\)
- Coefficient of \(x\): \(ad + bc = -2\)
- Constant term: \(bd = 0\)
From \(bd = 0\), either \(b\) or \(d\) is zero. Let us set \(b = 0\) (we can check alternate cases later), yielding:
- Thus, \(bd = 0\) is satisfied.
Now substituting \(b = 0\) into equations:
- \(ad = -2\)
- \(ac = 1\)
From \(ac = 1\), with \(c = 1/a\), substituting in \(ad = -2\): \[ ad = a\left(\frac{1}{a}\right)d = d = -2 \] Here, we get \(d = -2\) when \(b = 0\). Therefore, from \(ac = 1\), we can choose \(a = 1\) and \(c = 1\), which gives:
The values become: \((a, b, c, d) = (1, 0, 1, -2)\).
3. Third Polynomial:
Given:
\[ 2x^2 - 2x - 24 = (ax + b)(cx + d) \]
Dividing everything by 2, we have: \[ x^2 - x - 12 = (ax + b)(cx + d) \]
Expanding: \[ acx^2 + (ad + bc)x + bd \]
Comparing coefficients:
- \(ac = 1\)
- \(ad + bc = -1\)
- \(bd = -12\)
Again, \(ac = 1\) implies \(a\) and \(c\) can be \(1\) or \(-1\). Using \(a = 1\), we yield: \[ d + b = -1 \quad \text{(from \(ad+bc = -1\) results in this)} \]
So, like before, let \(d = -1 - b\) and substituting: \[ b(-1 - b) = -12 \Rightarrow -b - b^2 = -12 \Rightarrow b^2 + b - 12 = 0 \]
Factoring the quadratic gives: \[ (b - 3)(b + 4) = 0 \] Thus, \(b = 3\) or \(b = -4\).
If \(b = 3\): \[ d = -1 - 3 = -4 \]
If \(b = -4\): \[ d = -1 - (-4) = 3 \]
Now summarizing the values found:
- \((1, -2, 1, -4)\) or \((1, -4, 1, -2)\) from the first.
- \((1, 0, 1, -2)\) from the second.
- \((1, 3, 1, -4)\) or \((1, -4, 1, 3)\) from the third.
Final integers are:
- From first equation: \(a = 1\), \(b = -2\), \(c = 1\), \(d = -4\) (or similar variants).
- From second: \(a = 1, b = 0, c = 1, d = -2\).
- From third: Check \(a = 1, b = 3, d = -4\) as compatibly possible with previous results.
This concludes the evaluation of \(a, b, c, d\) for the polynomial equations presented.